Electrochemical Synthesis of Ammonium from Nitrates via Surface Engineering in Cu2O(100) Facets - Qin, Jiangzhou; Chen, Liuzhou; Wu, Kun; Wang, Xintao; Zhao, Quanlin; Li, Lei; Liu, Baojun; Ye, Zhengfang (ACS applied energy materials, 2022)
Revealing the reactivity of different exposed facets is crucial for designing highly effective electrocatalysts to selectively reduce nitrate (NO3 –) to ammonia (NH4 +). Herein, two dominant exposures of Cu2O(100) and Cu2O(111) facets are designed to explore the effects of interfaces on properties. Cu2O(100) achieved a relatively high NH4 + yield rate of 743 μg h–1 mgcat. –1 associated with a Faradic efficiency of 82.3% at −0.6 V vs the reversible hydrogen electrode (RHE), attributed to a relatively lower energy barrier (0.18 eV) for NH3 production than the Cu2O(111) surface (1.43 eV). In addition, 15N isotope-labeling experiments were used to quantitatively analyze the yield rate of NH4 + and further confirmed the reliability of nitrogen sources. This work provides reliable evidence to improve the selectivity of NO3 – to NH4 + by crystal facet engineering.